2017
DOI: 10.1039/c6cp08937b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide layers modified by light energetic ions

Abstract: In this paper, the effect of light ion irradiation on graphene oxide foil structure and composition was studied. Due to the excellent properties of graphene based materials suitable for application in electronics, optoelectronics, micro-mechanics and space technologies, the interaction of energetic ions with graphene based structures is worth studying. From the fundamental point of view, it is also interesting to get information about graphene oxide structure modification and the possible functional properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…This finding is also in agreement with the XPS results, where only slight decrease of C-O bond and slight increase of C-C bond can be observed. The similar results, but with higher degree of GO reduction, can be observed after light (He, H) ion irradiation with MeV energy and fluencies up to ion fluence 1.0x10 14 cm -2 [17]. The ion irradiation with higher fluencies and heavy ions leads to the more pronounced sample amorphization and distortion of the sp 2 carbon bond angle, giving origin to non-six membered rings [30].…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…This finding is also in agreement with the XPS results, where only slight decrease of C-O bond and slight increase of C-C bond can be observed. The similar results, but with higher degree of GO reduction, can be observed after light (He, H) ion irradiation with MeV energy and fluencies up to ion fluence 1.0x10 14 cm -2 [17]. The ion irradiation with higher fluencies and heavy ions leads to the more pronounced sample amorphization and distortion of the sp 2 carbon bond angle, giving origin to non-six membered rings [30].…”
Section: Resultssupporting
confidence: 57%
“…5 presence of the five different carbon bonding states; C=C (284.4) and C-C (285.4) in the sp 2 , C-O (286.3), C=O (288.0) in the carbonyl C and O-C=O (289.0) in the carboxylate C [9]. In the pristine GO foil dominates the C=C peak in sp 2 hybridized carbon, whereas the C-O peak that in GO commonly dominates is in the current sample reduced [17]. These indicate the significant degree of reduction of as-prepared GO foil that can be connected with warm drying during GO foil preparation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, fresh graphene oxide (GO) foil was synthesized like-Hummers method as reported in Ref. [13] to prepare GO thin foils. The evaluation of GO density was carried out by a Mettler Toledo MicroBalance with ± 1µg absolute accuracy in standard microbalance weighing technique.…”
Section: Methodsmentioning
confidence: 99%